The TranSys: Information system for small and medium scaled transportation companies / Chung Chee Chuan - Chung, Chee Chuan (2003)
Logistics affect almost every sphere of human activities. One major component of logistics process is the movement of goods from point-to-point to point-of-consumption, and perhaps their return as well. Transportation is often the single largest cost in the logistics process. Therefore, it is important component that must be managed effectively. The TranSys, a transportation system is basically a application which targets logistics practitioner especially those who provide trucking service to automate and structure the delivery process to help ensure that products and services meet or exceed customer's exact requirements. The convenience of the TranSys is to bring automation in scheduling trucks and drivers to delivery items to destination. Embedded in this system was cost analysis, a powerful yet versatile module which help management to keep in touch with the most expensive cost component in logistics. The intelligence of the system will be placed on the server where all calculations and business rules are applies. The TranSys is planning to be developed by using Microsoft Visual Basic 6.0 and Crystal Report 8.5 technologies on the Window 2000 Server platform with Microsoft SQL Server 2000 as its back-ends. With the latest and powerful ActiveX Data Objects 2.6 technology, the system is not only expected to be workable, but also highly efficient in terms of execution speed and response time. The system design is dynamic and supporting concurrent users to interact with the system over the 2-tier traditional client-server architecture.